MODELINTERVENSI PENDIDIKAN RAMAH ANAK BAGI ORANG TUA SISWA SD NEGERI SECANG I DAN SMP NEGERI TEMPURAN I KABUPATEN MAGELANG - Senowarsito .; Listyaning S; Suwarno Widodo; Arso Setyaji (Universitas PGRI Semarang, 2014)
The aims of the research were to identify understanding of parents, the implementations of 3P (Provision, Protection, and Participation) in family, and identify the caharacteristics of parents, as well as developing the intervention child-friendly model. The method of research was conducted Research and Development (R&D). The population of research was the parent of students in SD Negeri Secang I dan SMP Negeri 1Tempuran, Distric of Magelang and purposive technique sampling. Data collection was conducted with triangulation data (observation, interview, and questionnaires). The result of the research were (1) the understanding of parents about child-friendly was still limited toward duty and the obligation parents to students; (2) the form of implementation 3P (Provision, Protection, and Participation) was implemented of parents maximum yet because the diversity of understanding by the parents; (3) the parents of students in SD Negeri Secang 1 and SMP Negeri 1 Tempuran, district of Magelang still faced the obstacles in implementing child-friendly in their family; (4) the diversity of characteristic of parents mainly education and economic background. Keywords: intervention model, child-friendly, education, parents